QIYAS SEBUAH METODE PENGGALIAN HUKUM ISLAM - AZHARI, FATHURRAHMAN (Syariah: Jurnal Hukum dan Pemikiran, 2013)
As an Islamic law argument, qiyas is a solution to various legal cases which are not explicitlymentioned in religious texts. Imam Syafii is the initiator of the concept of qiyas. In his view, variouslegal cases found in Muslim society which are not obviously regulated in religious texts can be solvedthrough qiyas, either in the form of strong qiyas or weak qiyas. Anybody who knows Arabic, Islamiclaw contained in the Quran, the prophetic tradition, the opinions of the early generation of the ulama,consensus and controversies among them, having high intellectual capacity and sharp analysis inwhich he or she can identify obscured facts, can become an al-qais. the qiyas should consist of fourelements the al-ashl, the original law derived from the text, the al-far, an the legal al-illah. An qiyasshould not go beyond relegious texts, because it is merely an exension of them